PENGARUH GAYA KEPEMIMPINAN MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS PEMBERDAYAAN MASYARAKAT DAN KAMPUNG DI KABUPATEN BERAU - Ayyub, Muh Amrizal; Hasnawati, Hasnawati (STIE Muhammadiyah Tanjung Redeb, 2017)
ABSTRCAK The purpose of the research is whether the style is leadership, motivation and workplace influence the performance of the state civil apparatus thr / on the community empowerment and round kabaputen berau. Methods used in research is quantitative methods Judging from the results of the Hypothesis Test. Based on the results of Test F that is Fcount with a value of 10.750> from Ftable with a value of 3.26 there is an influence between the Independent X variable on the Dependent variable Y. From the results of the t test it is known that there is an influence between each independent variable on the dependent variable. Based on the Leadership Style variable, the value of tcount is 2,291> from the value of t table 2,02534, it can be seen that there is an influence between Variable X1 to Variable Y, then for Motivation variable with tcount 2,313> from the value of t table 2,02534 it can be seen that there is an influence between variable X2 to variable Y, then the Work Environment variable with tcount 2.447> from the value of t table 2.02534, it can be seen that there is an influence between variables X3 to variable Y. Keyword :Syle of leadership, motivation and work environment